2020
DOI: 10.1007/s40415-020-00584-w
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiological responses of tomato phytochrome mutants under sun and shade conditions

Abstract: Phytochromes (PHYs) have long been associated with classic photomorphogenic responses and recently implied with the regulation of plant productivity. We aimed to characterize these links in an important agronomic crop such as tomato (cv. Moneymaker) by evaluating biomass partitioning and morphophysiological parameters related to productivity under distinct light conditions in phyA, phyB1 and phyB2 tomato mutants. Under sun, PHY mutants presented lower leaf biomass during the vegetative phase the same way as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…It was also observed that phyB1 and phyB2 decreased the shoot and whole plant biomass production (Figure 4A,C), highlighting the importance of tomato phyB as a positive regulator of pigment production, nutritional efficiency and growth. This was an expected result, seen that active phytochromes control the allocation of biomass, and its deficiency may reduce vegetative biomass accumulation in tomato plants (Mereb et al 2020).…”
Section: Complete Nutrient Solutionsupporting
confidence: 54%
See 1 more Smart Citation
“…It was also observed that phyB1 and phyB2 decreased the shoot and whole plant biomass production (Figure 4A,C), highlighting the importance of tomato phyB as a positive regulator of pigment production, nutritional efficiency and growth. This was an expected result, seen that active phytochromes control the allocation of biomass, and its deficiency may reduce vegetative biomass accumulation in tomato plants (Mereb et al 2020).…”
Section: Complete Nutrient Solutionsupporting
confidence: 54%
“…The deficiency of phyB1 and phyB2 in tomato plants results in reduced chlorophyll content and biomass production during the vegetative phase, indicating that this photoreceptor acts in the control of chlorophyll synthesis in addition to dry weight production (Mereb et al 2020). For instance, the participation of phytochromes in plant nutrition has been shown in Arabidopsis, where phytochrome B (phyB) induces the activation of genes encoding for phosphorus transporters.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PHYB2 is highly expressed in fruits and marked accumulation of PHYA has also been verified during ripening ( Alba et al, 2000b ; Bianchetti et al, 2018 ). Finally, PHYE functions are related to shade avoidance responses ( Schrager-Lavelle et al, 2016 ), while specific roles for PHYF remains elusive ( Mereb et al, 2020 ). Tomato phyA , phyB1 , and phyB2 knockout mutants have been well characterized over the last two decades and several phenotypes associated with light perception deficiency in seedlings and vegetative organs have been described ( Kerckhoffs et al, 1996 , 1999 ; Behringer and Lomax, 1999 ; Weller et al, 2000 ; Bianchetti et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…phyB1 leaf area and biomass were also higher than WT under water deficit (Figure 1). The loss of phytochromes leads to an etiolated phenotype in tomato, with preferential biomass allocation into stems (Mereb et al, 2020), a condition synergically intensified by drought stress in phyB1 plants. PHYB1 seems to play a central role in controlling such an allocation pattern since its overexpression leads to biomass accumulation into roots (Husaineid et al, 2007), while it was not verified in the phyB1 mutant.…”
Section: Discussionmentioning
confidence: 99%